Foreign Grant Support for Projects in the Context of R&D Structure and Performance in Ukraine - Malitsky, B.A. (Наука та наукознавство, 2015)
Information about peculiarities and trends of grant form of R&D financing in Ukraine is given. It is emphasized that it was developing in Ukraine along with rapid decline in R&D financing, which entailed mainly “utilitarian” view of foreign grants, although they should be regarded as, first and foremost, as an effective means for internationalization of the national R&D system. Main reasons for intensification of grant form of foreign support to national R&D are highlighted. Factors determining participation of Ukrainian researchers in international projects with grant financing are outlined: the performance of domestic research potential and the thematic conformity of R&D conducted in Ukraine and beyond Ukraine. Estimates on publication activity of Ukrainian researchers, derived using domestic and international databases, and results of a comparative analysis of the publication activity of researchers from Ukraine and selected European countries are given. The problem of grant R&D financing inside Ukraine is discussed. Наведено інформацію про особливості та тенденції грантової форми фінансування в Україні. Підкреслено, що вона розвивалась в Україні на тлі різкого зниження витрат на науку, що визначило в основному «утилітарне» ставлення до зарубіжних грантів, хоча їх насамперед необхідно розглядати як ефективний засіб інтернаціоналізації національної наукової системи. Наведено основні причини активізації грантової форми зарубіжної підтримки національних НДДКР. Розкрито фактори, що визначають ступінь участі українських вчених у міжнародних проектах з грантовим фінансуванням: рівень розвитку наукового потенціалу країни та відповідність між тематичним профілем досліджень в Україні та світі. Наведено оцінки публікаційної активності українських учених на основі вітчизняної та міжнародної баз даних, а також результати порівняльного аналізу публікаційної активності вчених України та деяких європейських країн. Висвітлено проблему розвитку грантової форми підтримки НДДКР усередині України. Приведена информация об особенностях и тенденциях грантовой формы финансирования науки в Украине. Подчеркнуто, что она развивалась в Украине на фоне резкого снижения расходов на науку, что предопределило в основном «утилитарное» отношение к зарубежным грантам, хотя их прежде всего необходимо рассматривать как эффективное средство интернационализации национальной научной системы. Приведены основные причины активизации грантовой формы зарубежной поддержки национальных НИОКР. Раскрыты факторы, определяющие степень участия украинских ученых в международных проектах с грантовым финансированием: уровень развития научного потенциала страны и соответствие между тематическим профилем исследований в Украине и мире. Приведены оценки публикационной активности украинских ученых на основе отечественной и международной баз данных, а также результаты сравнительного анализа публикационной активности ученых Украины и некоторых европейских стран. Освещена проблема развития грантовой формы поддержки НИОКР внутри Украины.